Google speaks : secrets of the world's greatest billionaire entrepreneurs, Sergey Brin and Larry Page - Lowe, Janet (John Wiley & Sons, 2009)
"An up-close look at the people and philosophies behind one of the most important new companies of our time, Google Speaks is an engaging and informative look at one of the most important companies of the twenty-first century. It reveals the amazing story behind Google, a company that in less than 15 years has become a global household name and, in the process, created a new model for corporate responsibility and employee relations. Lowe explores the values that drive Google's founders and discusses how they have created a culture that fosters creativity and fun, while at the same time, keeping Google at the forefront of technology through large, relentless R & D investments and imaginative partnerships with organizations such as NASA. This book also addresses controversies surrounding Google, such as copyright infringement, antitrust concerns, and personal privacy."--Jacket